1996
DOI: 10.1097/00003246-199607000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal permeability and absorptive capacity in sepsis

Abstract: Patients with acute sepsis exhibit increased gastrointestinal permeability and decreased gastrointestinal functional absorptive capacity in comparison with healthy control subjects. These abnormalities may contribute to the pathophysiology of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 38 publications
8
50
0
3
Order By: Relevance
“…The L/R ratio is considered a measure of intestinal permeability, whereas the XYL/OMG and RHA/OMG ratios are used as indices of epithelial absorptive capacity and mediated cellular transport, respectively. L/R ratios, XYL/ OMG ratios, and RHA/OMG ratios of Յ 0.02, 25,26 Ն 0.28, 27 and Ն 0.65, 28 respectively, are considered normal.…”
Section: Urinary Excretion Ratios Of Differential Sptsmentioning
confidence: 99%
“…The L/R ratio is considered a measure of intestinal permeability, whereas the XYL/OMG and RHA/OMG ratios are used as indices of epithelial absorptive capacity and mediated cellular transport, respectively. L/R ratios, XYL/ OMG ratios, and RHA/OMG ratios of Յ 0.02, 25,26 Ն 0.28, 27 and Ն 0.65, 28 respectively, are considered normal.…”
Section: Urinary Excretion Ratios Of Differential Sptsmentioning
confidence: 99%
“…Arti®cial ventilatory support is instituted and the cardiovascular system is supported with inotropes and vasopressors. Failure of gastrointestinal function, absorption and motility (Johnston et al, 1996), necessitates the use of arti®cial nutritional support, parenteral or enteral, and if renal failure supervenes renal replacement therapy such as haemo®ltration or haemodialysis is required. Rates of urinary nitrogen excretion in MOF are in the region of 20 ga24 h (Streat et al, 1987;Finn et al, 1996;Clark et al, 1996).…”
Section: Substrate Mobilisationmentioning
confidence: 99%
“…High levels of sympathetic activity impair gastric emptying so enteral feeding may have to be given beyond the pylorus (Johnston et al, 1996), a technique that carries risks and may limit the quantities that can be given. Because of impaired gastrointestinal function it may not be possible to provide all the needed nutrients enterally (Kemper et al, 1992).…”
Section: The Delivery Of Nutritional Support In the Critically Illmentioning
confidence: 99%
“…For example, clinical correlative studies have established that defective intestinal barrier function is frequently observed in septic patients [9,10]. Here, we characterize bowel pathology after LPS treatment of p50 and 3X mice.…”
Section: Introductionmentioning
confidence: 97%